Disengagement Processes Within an Early Intervention Service for First-Episode Psychosis: A Longitudinal, Qualitative, Multi-Perspective Study - Tindall, Rachel; Simmons, Magenta; Allott, Kelly; Hamilton, Bridget (Frontiers in Psychiatry, 2020)
Background: Specialized early intervention services for first-episode psychosis have been well established in many countries to meet the unique needs of this group. However, with high drop-out rates, these services would benefit from understanding the factors that influence a person’s decision to engage with, or disengage from, them. No research has explored the experiences of engagement and disengagement over time, from the perspectives of the person who experienced a first-episode psychosis, their caregiver and their clinician. This information is crucial to help services better respond to the needs of the people using them. The aim of this study was to understand what causes and maintains periods of disengagement from early intervention services for first-episode psychosis over time. Methods: Using a longitudinal, qualitative approach, young people, their caregivers and their clinicians were followed through their first year with an early intervention service for first-episode psychosis in Melbourne, Australia. Qualitative interviews were completed between 3-9 weeks, 4-7 months and 11-15 months after entry to the service (or at discharge if earlier). Trajectory analysis was used to understand the data. Results: Qualitative interviews were conducted with 24 participants (55 interviews). Young people were aged 15 to 24 years, came from a variety of cultural backgrounds and had various psychotic diagnoses. Three major processes were identified that, over time, led to periods of service disengagement: a mismatch between service model and individual presentation (service mismatch), a lack of shared purpose (aimless engagement) and responses to individual circumstances (reactive disengagement). Conclusion: Triangulating experiences of engagement across young people, caregivers and clinicians allows for a comprehensive understanding of what precipitates service disengagement. This study demonstrates how early intervention services for first-episode psychosis are meeting the needs of young people and caregivers, and what areas warrant improvement. The needs of service users and patterns of disengagement vary. In turn, services must be flexible and responsive to individual circumstances. The results of this study recommend that local and international policies move away from diagnostically driven models of care, to better provide an inclusive treatment service for people with transdiagnostic mental health presentations.